2007
DOI: 10.1902/jop.2007.060494
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Therapy in the Non‐Surgical Treatment of Aggressive Periodontitis: A Preliminary Randomized Controlled Clinical Study

Abstract: PDT and SRP showed similar clinical results in the non-surgical treatment of aggressive periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
199
2
38

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(245 citation statements)
references
References 63 publications
6
199
2
38
Order By: Relevance
“…Recently, two papers found favorable results as the use of PDT in the AP treatment [33][34] . Nevertheless, further studies are needed to prove the real importance of this therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two papers found favorable results as the use of PDT in the AP treatment [33][34] . Nevertheless, further studies are needed to prove the real importance of this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, de Oliveira et al found clinical outcomes similar to SRP and PDT in PD sites ≥ 5 mm after 3 months of follow-up 33 . The tumor necrosis factor (TNF-α) and the ligand receptor activator of nuclear factor kappa B (RANKL) are cytokines related to connective tissue and bone destruction.…”
Section: Photodynamic Therapymentioning
confidence: 97%
“…without any mechanical debridement). 42,43 (Table 2). While one study has found in deep pockets (PD ≥ 7 mm) statistically significant improvements in terms of PD reduction and CAL gain and significantly less periodontal pathogens of the red and orange complex and IL-1β/IL-10 ratio following treatment with PDT, 41 the other study has failed to reveal any statistical significant differences in the evaluated clinical and microbiological parameters between the treatments 40 (Table 2).…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
“…Dessa forma, as três concentrações do azul de toluidina e azul de metileno utilizadas foram 0,05 mg/ml (BERAKDAR et al, 2012;BALATA et al, 2013;PINHEIRO et al, 2010) ,0,1 mg/ml (AL-ZAHRANI et al, 2009;GE et al, 2011;NORO FILHO et al, 2012;THEODORO et al, 2012;BASSIR et al, 2013;FRANCO et al, 2014;MONGARDINI;DI TANNA;PILLONI, 2014) e 10 mg/ml (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008;CHONDROS et al, 2009;DE OLIVEIRA et al, 2009;LULIC et al, 2009;POLANSKY et al, 2009;SIGUSCH et al, 2010;CAPPUYNS et al, 2012;GIANNOPOULOU et al, 2012;NOVAES et al, 2012;ANDRADE et al, 2013;CAMPOS et al, 2013;LUCHESI et al, 2013;SOUZA et al, 2013;ARWEILER et al, 2014;BETSY et al, 2014;KOLBE et al, 2014;MACEDO et al, 2014;MOREIRA et al, 2014;PETELIN et al, 2014;QUEIROZ et al, 2014;ALWAELI;KHATEEB;AL-SADI, 2015;QUEIROZ et al, 2015). Apesar dos resultados do teste de concentração dos corantes, onde a concentração de 10mg/ml foi a única efetiva para o metileno e a de 5 e 10mg/ml foram as bactericidas para o toluidina, optamos por testar novamente as três concentrações mais comum na literatura acima citada.…”
Section: Discussionunclassified
“…Outros estudos também aplicam essa potência (BRAUN et al, 2008;RÜHLING et al, 2010;GIANNELLI et al, 2012;GIANNOPOULOU et al, 2012;BALATA et al, 2013;DILSIZ;CANAKCI;AYDIN, 2013;ALWAELI;KHATEEB;AL-SADI, 2015). Porém ,outro valor de potência frequentemente encontrado é entre 60 mW e 75 mW (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008;CHONDROS et al, 2009;DE OLIVEIRA et al, 2009;LULIC et al, 2009;POLANSKY et al, 2009;SIGUSCH et al, 2010;ANDRADE et al, 2013;CAMPOS et al, 2013;LUCHESI et al, 2013;SOUZA et al, 2013;BETSY et al, 2014;CHITSAZI et al, 2014;FRANCO et al, 2014;KOLBE et al, 2014;MACEDO et al, 2014;PETELIN et al, 2014;QUEIROZ et al, 2014;QUEIROZ et al, 2015). Por isso optou-se por testar dois valores de potência: 70 e 100 mW.…”
Section: Discussionunclassified